2017
DOI: 10.1503/cjs.001516
|View full text |Cite
|
Sign up to set email alerts
|

Physician extenders on surgical services: a systematic review

Abstract: Background: With the introduction of resident duty hour restrictions and the resulting in-house trainee shortages, a long-term solution to ensure safe and efficient patient care is needed. One solution is the integration of nurse practitioners (NPs) and physician assistants (PAs) in a variety of health care settings. We sought to examine the use of NPs and PAs on surgical/trauma services and their effect on patient outcomes and resident workload. Methods:We performed a systematic review of EMBASE, Medline, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…Evidence from North America suggests that similar factors have supported the inclusion of PAs in acute medical/surgical teams. 133,152,153 As part of an innovation and change process, 154 many participants within the hospitals identified the benefit of having clinical leadership, ongoing clinical champions for PAs and visible executive-level support (see Chapters 4, 7 and 9). This has previously been described in relation to one acute hospital unit in England.…”
Section: The Extent Of the Adoption And Deployment Of Physician Assocmentioning
confidence: 99%
“…Evidence from North America suggests that similar factors have supported the inclusion of PAs in acute medical/surgical teams. 133,152,153 As part of an innovation and change process, 154 many participants within the hospitals identified the benefit of having clinical leadership, ongoing clinical champions for PAs and visible executive-level support (see Chapters 4, 7 and 9). This has previously been described in relation to one acute hospital unit in England.…”
Section: The Extent Of the Adoption And Deployment Of Physician Assocmentioning
confidence: 99%
“…12,13 Other studies quantifying the effects of APPs in field found APPs increase the efficiency of attending surgeons. [14][15][16][17] The investigation of the impact of APPs on resident education, particularly surgical resident education, has been limited. Surveys of both surgical faculty and residents have acknowledged that APPs offer benefits in managing the clinical workload while posing a potential threat to resident education.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, faculty face constant pressure to be clinically productive, and APPs have been demonstrated to improve surgeon efficiency in multiple studies. [14][15][16][17] APPs, residents, and faculty is the next critical step in this process. Assessing, and then periodically reassessing, the team dynamic as well as satisfaction with the responsibilities of the team members ensures continued satisfaction with these roles over time.…”
Section: Commentmentioning
confidence: 99%
“…One study found that patients in ICUs with nurse practitioners and physician assistants had lower mean acute physiology scores and mechanical ventilation rates [5]. Another study examining the use of nurse practitioners and physician assistants on adult surgical and trauma services also found that LOS decreased but found that mortality and morbidity were unchanged [6]. With some research showing that extenders had a positive effect when introduced in certain hospital settings, it is worthwhile to determine if there a significant treatment outcome between physician extenders only and both residents and extenders.…”
Section: Introductionmentioning
confidence: 99%